Reinvigorating growth in developing countries : lessons from adjustment policies in eight economies - Goldsbrough, David... [et al] (IMF WashingtonUS, 1996)
Summarizes the long-term trends in growth and investment. Discusses the evidence from cross-country econometric work on factors influencing long-term growth and examines the role of macoreconomic policies. Looks at factors explaining the path of private investment and saving. Explores the role of external financing and sets out specific policy conclusions and lessons for the design of adjustment policies.